2005
DOI: 10.1111/j.1365-3156.2005.01521.x
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of multidrug‐resistant Mycobacterium tuberculosis isolates in Georgetown, Guyana

Abstract: SummaryEmergence of multidrug-resistant (MDR) Mycobacterium tuberculosis isolates constitutes a threat to public health worldwide. This study aimed at acquiring first epidemiological data for Guyana. Thirty-six M. tuberculosis isolates from patients of the Georgetown Chest Clinic were subjected to susceptibility testing on solid agar and in broth media. Resistance to at least one first-line drug was observed in 8 (22.2%, 95% confidence interval 8.3-36.1%) and simultaneous resistance to rifampicin and isoniazid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
2
1
0
Order By: Relevance
“…This finding is in agreement with a previous study that reported resistance to at least one anti-TB drug in 22.2% of the tested Guyanese MTBC isolates and MDR-TB in 11.1% of the strains [21]. The authors attributed these high levels of resistance to inadequate monitoring and followup of patient treatment and to poor management of the TB control program.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in agreement with a previous study that reported resistance to at least one anti-TB drug in 22.2% of the tested Guyanese MTBC isolates and MDR-TB in 11.1% of the strains [21]. The authors attributed these high levels of resistance to inadequate monitoring and followup of patient treatment and to poor management of the TB control program.…”
Section: Discussionsupporting
confidence: 92%
“…This data confirms the continued existence of drug resistance in Guyana, as an earlier report by Menner et al, 2005 [40] also reported a high frequency of drug resistance in this country with 22.2% of the isolates tested showing resistance to at least one anti-tuberculosis drug and 11.1% showing resistance to INH and RIF [40]. The reason for the continued persistence of MDR-TB in Guyana according to Menner et al is the lack of human resources to adequately follow up and monitor patient treatment as well as poor management of the tuberculosis control programme [40]. In this present study similar results were seen as 20.5% of isolates tested showed resistance to at least one anti-TB drug and 14.5% showed resistance to INH and RIF (MDR-TB).…”
Section: Profiles Of Drug Susceptibility Patterns Of Mycobacterium Tusupporting
confidence: 78%
“…These omissions may result in an underestimate of the burden of resistant disease and preclude design of effective standardized regimens. 52 The foregoing summary results also mask significant variability (Table 1 [53][54][55][56][57][58][59][60][61][62][63][64] ). * In some parts of the world, like the former Soviet Union and eastern Europe, the percent of new and previously treated TB cases with Source population and sampling strategy are specified for those countries or regions for which sampling was conducted.…”
Section: Epidemiology Of Mdr-tbmentioning
confidence: 99%